The Geographical Distribution of Wheat Crop in Wasit Province for the period ( 2003 - 2010 ) - كوثر ناصر عباس (College of Education for Women, 2019)
This study focuses on the basics of cultivation and production of the Wheat Crop in Wasit Province ; in order to reveal the reality of the geographical distribution of its cultivation and production. Wheat is the most important field crops cultivated in Wasit province, as it has vast possibilities for expansion in growing and production, in which agriculture conducted in a year and left in other , then changing this method would increase cultivated area of it to nearly doubled, as well as the possibility of increasing average yields in Donam by using improved seeds, fertilizer, with the availability of water lever machines, especially wheat is grown in areas of rivers abutment. The study showed the spread of the crop in all districts of the province, where Essaouira District got highest average planted area with the highest rate of production, and then Numaniyah District ranked second in terms of planted area, but in production volumes Azizia District came in second rank, and all that give an evidence of providing space potable for agriculture as well as the availability of modern irrigation projects.